2005
DOI: 10.2165/00002512-200522090-00005
|View full text |Cite
|
Sign up to set email alerts
|

Adverse Drug Reactions in an Elderly Hospitalised Population

Abstract: A significant prevalence of ADRs was found among hospitalised elderly people. The risk factors associated with ADRs in this population included use of drugs considered to be inappropriate for that population, number of previous diagnoses and number of administered drugs. More appropriate drug prescription could avoid part of this burden of disease by minimising preventable ADRs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
192
7
31

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 304 publications
(245 citation statements)
references
References 47 publications
15
192
7
31
Order By: Relevance
“…However, there is controversy regarding whether the use of PIM is a risk factor for hospital admission [10,12,13,16] . In this study, one out of four (15/59) patients who reported taking PIM had been admitted to hospital for ADR.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there is controversy regarding whether the use of PIM is a risk factor for hospital admission [10,12,13,16] . In this study, one out of four (15/59) patients who reported taking PIM had been admitted to hospital for ADR.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the identified PIM, 55.0% of them were related to ADR, of which 73% (8 / 11) are frequently prescribed for older people, according to the literature: digoxin [8][9][10]14,16,29] , amitriptyline [9,10,13,14,16,29] , amiodarone [8][9][10]14,16,29] , diazepam [10][11][12][13][14] , methyldopa [9,10,12,17,29] , cimetidine [9][10][11]16,29] , fluoxetine [9,10,14,16,29] and short-acting nifedipine [8][9][10]14,16] . Data suggest that prescribers do not know the drugs considered PIM for older people, since there are safer alternatives for most inadequate medications identified in the present study, such as selective serotonin reuptake inhibitors or serotonin-specific reuptake inhibitor (e.g.…”
Section: Albert Et Al (2010)mentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of such effects may reach 19%, and two thirds of them can be avoided. 2 In Brazil, drug adverse effects among hospitalized patients have been studied by using a longitudinal approach, 3,4 reviewing medical files retrospectively 1 or using the hospital database of the Sistema Único de Saúde (SUS -National Health System). 5 The objective of the present study was to analyze the results from a strategy of monitoring drug adverse effects that was applied in a public hospital.…”
Section: Introductionmentioning
confidence: 99%
“…Este riesgo aumenta con la fragilidad del paciente y con la polifarmacoterapia (3). Las reacciones adversas a medicamentos constituyen una causa importante de morbimortalidad de los pacientes, un reto para el profesional de la salud y un problema de salud pública para la ciudad y el país (4,5).…”
unclassified